Pengaruh Tipe Mobil Terhadap Harga dan Kapasitas Mesin di Belarus Dengan Pendekatan Metode Manova - Liana Putri, Natasya; Pingit Wulandari, Sri; Handayani, Melita (Green Publisher Indonesia, 2024)
Belarus is a country on the European Continent that continues to develop modern technology, especially in the field of the transportation industry. Supported by people's consumption patterns that tend to be consumptive where the demand for goods can affect the country's economy if not controlled properly, one of which is the use of cars. The high interest of the public in the use of cars is influenced by the design of the body type. Body type plays an important role in determining consumer preferences. The design of the car body type also affects the selling price. Engine capacity is also closely related, where larger vehicles typically have larger tanks. Therefore, it is important to analyze the influence between car body type and price and car engine capacity in Belarus using the multivariate analysis of variance (MANOVA) method. Data analysis starts from describing the characteristics of variables, then conducting MANOVA assumption testing starting from multivariate normality testing with Q-Q plot and T-proportion test, independence correlation test test with barlet test, and homogeneity test with box's m test. Followed by the MANOVA test on the body variable on the price and capacity of the car engine and after that the LSD test. The results of the price characteristics and the capacity of the car engine were obtained by one and two outliers, respectively, and the shape of the boxplot was asymmetrical The most observed type of car was the universal type. The results of the MANOVA assumption test show that the data is normally distributed multivariate, dependent, and has a homogeneous covariance variance matrix. The results of the MANOVA test show that there is at least one type of car that has a significant influence on the price and capacity of the car engine. The LSD test results show the type of car based on the price of the car that there is no difference between the average car type 1, 2, 3, 4.